The leptin transduction pathway may be targeted against invasive ductal carcinoma of breast - M.Rahman, Shaikh; Abdulrazzaq, Saad Mohammed; Mohammad Amjad, Nasser; Al-Kubaisi, Muna Khaleel Dheyab; Harun, Norra; Nafie, Emad M. (American Association For Cancer Research (AACR), 2018)
Despite some controversies, it is generally suggested that obesity imparts a higher risk of breast cancer, the most common cancer among women all over the world. Since obese people usually have higher serum levels of leptin, a hormone secreted by white adipose tissue, the hormone is suspected as the link between adiposity and breast cancer. In this study we tried to explore a possible causal association of obesity and serum leptin with breast cancer by studying a sample of healthy controls and patients from Malaysian population. The control group comprised 40 women with negative mammogram for breast cancer, while the patient group comprised 51 women with invasive ductal carcinoma (IDC) of breast, who were going to be operated. We measured the common obesity parameters, confirmed the diagnosis of IDC of breast in the patients by standard histopathologic examination using hematoxylin and eosin stain, and estimated serum leptin levels using ELISA procedure. We estimated both pre- and postoperative samples of leptin from the patient group. Our results showed a highly significant difference in the serum leptin level between the control group and the patient group with a mean of 20.59 ± 14.4 ng/ml and 38.71 ± 12.2 ng/ml, respectively, having a P value of < 0.001. Our study showed no difference between the pre- and postoperative serum leptin levels in the patient group (P = 0.414). We found no significant difference between body mass index (BMI) of the control and the patient groups (P=0.699), and while in the control group there was strongly positive correlation between serum leptin level and BMI (rs = 0.598, P < 0.01), the patient group showed a positive but much weaker correlation (rs = 0.217, P > 0.05). Our results suggest that compared to BMI, serum leptin has a much stronger association with IDC; since the source of high leptin in serum is not breast cancerous tissue, leptin cannot be a marker for IDC of breast; however, the hormone most likely is causally associated with the tumorigenesis of breast cancer. The results also indicate that obesity, as indicated by BMI, is weakly associated with IDC; however, broader studies with much larger sample sizes are needed to draw any definitive conclusion. We hypothesize that reducing leptin levels, blocking its downstream tissue specific signal transduction, and/or blocking the upstream leptin receptor pathway might help in the prevention and therapy of breast cancer.